VisR: terms and conditions visualization using icons for Malaysia online shopping websites / Faten Farhana Mazlan - Mazlan, Faten Farhana (2016)
“Terms and Conditions Visualization using Icons for Malaysia Online Shopping Website” is an application build on bookmarklet to help online shopping customers identify the important things that must be read before buying the products. Reasons that people do not know terms and conditions because the way that it presented with a lots of jargons, long textual explanations and lot of paragraph. One of the ways to help user to understand is through visualization using icons. Visualization is a technique for creating images, diagrams or animations to present the information in the form of easy way for user to understand it. It is an effective way for present Terms and Conditions. The objective of this project is to identify techniques to better represent terms and conditions in simplified manner. The other objectives are to design the simplified terms and conditions and develop the bookmakrlet. This project abstracted the terms and conditions of online shopping websites like Zalora, Lazada, Shashinki, Fashion Valet and Uniqlo under six topics. The six topics include payment, delivery, cancellation, warranty, force majeure clause and return. The information’s in terms and conditions have been simplified into icons and arranged in easy by using bookmarklet. The last objective used is to test the application using functionality testing, usability testing and Flesch-Kincaid Testing. Research methodology using Agile method. The future work, this project can be improved by having the function to get the users feedback.